Magnetic Anisotropy in Pentacoordinate NiII and CoII Complexes: Unraveling Electronic and Geometrical Contributions - Cahier, Benjamin; Perfetti, Mauro; Zakhia, Georges; Naoufal, Daoud; El‐Khatib, Fatima; Guillot, Régis; Rivière, Eric; Sessoli, Roberta; Barra, Anne‐Laure; Guihéry, Nathalie; Mallah, Talal (Chemistry : a European journal, 2017)
The magnetic properties of the pentacoordinate [MII(Me4cyclam)N3]+ (Me4cyclam=tetramethylcyclam; N3=azido; M=Ni, Co) complexes were investigated. Magnetization and EPR studies indicate that they have an easy plane of magnetization with axial anisotropy parameters D close to 22 and greater than 30 cm−1 for the Ni and Co complexes, respectively. Ab initio calculations reproduced the experimental values of the zero‐field splitting parameters and allowed the orientation of the anisotropy tensor axes with respect to the molecular frame to be determined. For M=Ni, the principal anisotropy axis lies along the Ni−Nazido direction perpendicular to the Ni(Me4cyclam) mean plane, whereas for M=Co it lies in the Co(Me4cyclam) mean plane and thus perpendicular to the Co−Nazido direction. These orientations match one of the possible solutions experimentally provided by single‐crystal cantilever torque magnetometry. To rationalize the geometry and its impact on the orientation of the anisotropy tensor axis, calculations were carried out on model complexes [NiII(NCH)5]2+ and [CoII(NCH)5]2+ by varying the geometry between square pyramidal and trigonal bipyramidal. The geometry of the complexes was found to be the result of a compromise between the electronic configuration of the metal ion and the structure‐orienting effect of the Me4cyclam macrocycle. Moreover, the orientation of the anisotropy axes is mainly dependent on the geometry of the complexes. Nature and magnitude of the magnetic anisotropy of pentacoordinate NiII and CoII complexes [MII(Me4cyclam)N3]+ were studied by complementary magnetic measurements, high‐field EPR spectroscopy, single‐crystal torque magnetometry studies, and ab initio calculations, which unraveled the synergic effect of the electronic configuration of the metal ion and the structure‐orienting influence of the Me4cyclam tetradentate ligand (see figure).